Sustainability Of Markhor Trophy Hunting Programme In District Kohistan Pakistan - Ghafoor, Abdul (2014)
Trophy hunting is a form of sport hunting that has been practiced since hunting gatherer period. Usually, animals hunted as trophies have large weapons such as horns, antlers or tusks. Therefore, trophy animals are mostly males, and the animals most frequently considered as trophy species are ungulates. In 1983 the Wildlife Department of the Khyber Pakhtunkhwa province in Pakistan began the Chitral Conservation Hunting Programme, a trophy hunting programme for makhor (Capra falconeri cashmiriensis). Pemburuan trofi merupakan suatu bentuk sukan pemburuan yang diamalkan sejak berzaman lamanya. Biasanya, haiwan yang diburu sebagai trofi mempunyai tanduk atau gading, dan kebanyakannya adalah jantan. Pada tahun 1983, Jabatan Hidupan Liar Khyber, Wilayah Pakhtunkhwa, Pakistan memulakan Chitral Conservation Hunting Programme, iaitu suatu program pemburuan trofi bagi markhor (Capra falconeri cashmiriensis).